A new shuttle-shaped buckling-restrained brace. Theoretical study on buckling behavior and load resistance. (15th September 2017) - Guo, Yan-Lin; Zhu, Jing-Shen; Zhou, Peng; Zhu, Bo-Li
Highlights: A shuttle-shaped buckling-restrained brace (SS-BRB) is proposed. An SS-BRB significantly improves load-carrying efficiency and saves material. Equilibrium method is utilized to deduce the elastic buckling load of a pin-ended SS-BRB. The ultimate load-carrying capacity of an SS-BRB is directly proportional to restraining ratio. Lower limit of restraining ratio of SS-BRBs is derived theoretically and verified numerically. Abstract: This paper proposes a new type of buckling-restrained braces (BRBs), namely shuttle-shaped buckling-restrained braces (SS-BRBs). The proposed SS-BRB is composed of a circular steel tube as the inner core, and a shuttle-shaped thin-walled steel tube as the external restraining member. The space between them is filled by a steel-plate isolation system. The shuttle-shaped restraining member of the SS-BRB significantly improves load-carrying efficiency and saves material in its strength design. Moreover, the SS-BRB is more aesthetically appealing and can be utilized as an exposed BRB in long-span or spatial structures. In terms of the concept of restraining ratio of a BRB, no design method of an SS-BRB is available currently because it concerns the solution of the elastic buckling load of an SS-BRB. Therefore, the elastic buckling load of a pin-ended SS-BRB is initially studied by adopting the equilibrium method and is further verified through finite element (FE) method. The lateral displacement function of an SS-BRB, and the longitudinal stress at the extreme fiber of the external restraining member are derived by considering an initial geometric imperfection that is consistent with the first order overall buckling shape of the SS-BRB. A correction factor considering shear deformation has been incorporated for a more accurate prediction. The lower limit of the restraining ratio for a load-bearing type of SS-BRBs is further obtained based on yielding of the extreme fiber of the restraining member. Furthermore, the proposed formula has incorporated a strain hardening factor for the SS-BRB that experiences strain hardening of the core after its initial yielding. The proposed formulas have been validated through FE numerical analysis. The findings in this paper provide fundamentals to develop the design method for an energy-dissipation type of SS-BRBs.